Do Negative Appraisals of Unwanted Thoughts Predict Negative Outcomes? A Test of the Effect of Negative Appraisals across Thought Types. Issue 1 (April 2015) - Gentes, Emily; Ruscio, Ayelet Meron
Cognitive-behavioral and metacognitive theories propose that negative interpretations of normal intrusive or repetitive negative thoughts lead to symptoms of anxiety and depression. However, most research has been correlational and has examined only obsessional thoughts, despite similarities between theoretical models of obsessions and models of worry and rumination. In the present study, healthy participants were randomly assigned to receive negative, normalizing, or no feedback about their worried, ruminative, and obsessional thoughts to test the hypothesis that negative thought appraisals predict increased negative outcomes across thought types. Additional analyses determined whether preexisting beliefs about thoughts predicted outcomes, either alone or in interaction with experimental condition. Preexisting beliefs interacted with experimental condition to predict affective responses, with negative feedback having the expected effect only for individuals with preexisting negative beliefs about thoughts. Overall, results are consistent with a transdiagnostic model in which preexisting negative beliefs about thoughts act as a cognitive vulnerability in the face of specific, relevant environmental stressors.